Sustainability and Historic Preservation: Toward a Holistic View - Longstreth, Richard (University Press Copublishing Division, 2011)
Sustainability and Historic Preservation: Towards a Holistic View broadens the horizons of the mushrooming drive to correlate the objectives of these two spheres. To date, discussions of the relationship between historic preservation and sustainability have generally focused on the energy consumption of buildings. The nine chapters in this book show how that agenda can and should be expanded by examining many other facets of the environment, including agricultural lands, urban waterworks, irrigation systems, natural settings, an arboretum, and post-World War II suburbs. Written by specialists from a variety of disciplines—anthropology, architecture, landscape architecture, and urban history among them—the contents explore new realms in which historic preservation and sustainability can have common purpose. This book addresses subjects of concern to many persons engaged in both fields and argues the case for creating a greater spectrum of common ground between them.